A Covalent Reporter of β‐Lactamase Activity for Fluorescent Imaging and Rapid Screening of Antibiotic‐Resistant Bacteria. Issue 33 (8th July 2013) - Shao, Qing; Zheng, Yan; Dong, Xueming; Tang, Kai; Yan, Xiaomei; Xing, Bengang
Abstract Bacterial resistance to antibiotics poses a great clinical challenge in fighting serious infectious diseases due to complicated resistant mechanisms and time‐consuming testing methods. Chemical reaction‐directed covalent labeling of resistance‐associated bacterial proteins in the context of a complicated environment offers great opportunity for the in‐depth understanding of the biological basis conferring drug resistance, and for the development of effective diagnostic approaches. In the present study, three fluorogenic reagents LRBL1–3 for resistant bacteria labeling have been designed and prepared on the basis of fluorescence resonance energy transfer (FRET). The hydrolyzed probes could act as reactive electrophiles to attach the enzyme, β‐lactamase, and thus facilitated the covalent labeling of drug resistant bacterial strains. SDS electrophoresis and MALDI‐TOF mass spectrometry characterization confirmed that these probes were sensitive and specific to β‐lactamase and could therefore serve for covalent and localized fluorescence labeling of the enzyme structure. Moreover, this β‐lactamase‐induced covalent labeling provides quantitative analysis of the resistant bacterial population (down to 5 %) by high resolution flow cytometry, and allows single‐cell detection and direct observation of bacterial enzyme activity in resistant pathogenic species. This approach offers great promise for clinical investigations and microbiological research.